Emotion regulation shows an age- and sex-specific moderating effect on the relationship between chronic stress and cognitive performance - Novotný, Jan S; Srt, Luka; Stokin, Gorazd B (Scientific reports, 2024)
Despite the extensive knowledge about the effects of chronic stress on cognition, the underlying mechanisms remain unclear. We conducted a cross-sectional moderation analysis on a population-based sample of 596 adults to examine the age- and sex-specific role of emotion regulation (ER) in the relationship between chronic stress and cognitive performance using validated self-report questionnaires. While women showed no direct or moderated relationship between stress and cognition, men displayed a distinct age-related pattern where stress was negatively associated with poorer cognitive performance at older ages, and the onset of this relationship was detected earlier in men with ER problems. These results showed that suppression of emotions and lack of executive control of ER amplify the negative consequences of chronic stress and suggest that there are sex-specific differences in the decline of ability to cope with long-term exposure to stressors.
Keywords: emoční regulace; průzkumy a dotazníky; Cross-Sectional Studies; Surveys and Questionnaires; Female; Emotional Regulation; Adult; dospělí; Emotions; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; Cognition; průřezové studie; emoce; kognice